A Review of Management of Clostridium difficile Infection: Primary and Recurrence - Yasmeen Vincent; Arif Manji; Kathleen Gregory-Miller; Christine Lee (MDPI AG, 2015)
Clostridium difficile infection (CDI) is a potentially fatal illness, especially in the elderly and hospitalized individuals. The recurrence and rates of CDI are increasing. In addition, some cases of CDI are refractory to the currently available antibiotics. The search for improved modalities for the management of primary and recurrent CDI is underway. This review discusses the current antibiotics, fecal microbiota transplantation (FMT) and other options such as immunotherapy and administration of non-toxigenic Clostridium difficile (CD) for the management of both primary and recurrent CDI.